ANALISIS PENGARUH SUKU BUNGA, INFLASI, CAR, BOPO, NPF TERHADAP PROFITABILITAS BANK SYARIAH - Wibowo, Edhi Satriyo; Syaichu, Muhammad (Diponegoro Journal of Management, 2013)
Islamic Bank is well-known as a bank which is resistant to the global crisis that hitted Indonesia couple years ago. The performance of Islamic Bank could be maintained so that continuity of bussines also could be well maintained. Those performance could be measured by the size of the Islamic banking profitability. The factors affecting the profitability of Islamic banks used in this study are the interest rate, inflation, CAR, BOPO and NPF. While the purpose of this study was to determine the effect of interest rates, inflation, CAR, BOPO, and NPF toward the profitability of Islamic banks. The population used for the study is islamic banks whose financial statements have been published to Bank Indonesia from 2008 to 2011. For its Sampling in this study used purposive sampling obtained threeÂ  islamic banks. The data of this study used secondary data from the website of each bank and also Bank Indonesia. The method of data analysis which was used is multiple linear regression analysis. The results of this study indicate that the interest rate variabel has no effect on ROA, inflation had no effect on ROA, CAR had no effect on ROA and neither did NPF. While BOPO variabel had significant influence with negatif direction.